"Are perioperative opioids obsolete?" Proceedings of an IASP Acute Pain Special Interest Group Satellite Symposium September 25, 2016 Yokohama, Japan. (July 2017) - Carr, Daniel B.; Cohen, Robert I.
Abstract : This IASP Satellite Symposium surveyed opioid adverse effects upon patients and society, current and future drug and nondrug alternatives, and strategies to optimize postoperative outcomes through quality improvement.